1991
DOI: 10.1007/bf00167910
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of three threonine biosynthesis genes inCorynebacterium glutamicum and its influence on carbon flux in different strains

Abstract: The hom-thrB operon (homoserine dehydrogenase/homoserine kinase) and the thrC gene (threonine synthase) of Corynebacterium glutamicum ATCC 13,032 and the homFBR (homoserine dehydrogenase resistant to feedback inhibition by threonine) alone as well as homFBR-thrB operon of C. glutamicum DM 368-3 were cloned separately and in combination in the Escherichia coli/C. glutamicum shuttle vector pEK0 and introduced into different corynebacterial strains. All recombinant strains showed 8- to 20-fold higher specific act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 27 publications
2
88
2
Order By: Relevance
“…E. coli and all pre-cultures of C. glutamicum were grown aerobically in TY complex medium (Sambrook et al, 2001) at 37 and 30 uC, respectively, as 60 ml cultures in 500 ml baffled Erlenmeyer flasks on a rotary shaker at 120 r.p.m. For the main cultures of C. glutamicum, cells of an overnight pre-culture were washed with 0.9 % (w/v) NaCl (saline) and then inoculated into minimal medium (Eikmanns et al, 1991b) containing glucose or maltose at the concentrations indicated in Results. Cultivation was done aerobically at 30 uC as 250 ml cultures in a 'fedbatch-pro' parallel fermentation system from DASGIP, as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…E. coli and all pre-cultures of C. glutamicum were grown aerobically in TY complex medium (Sambrook et al, 2001) at 37 and 30 uC, respectively, as 60 ml cultures in 500 ml baffled Erlenmeyer flasks on a rotary shaker at 120 r.p.m. For the main cultures of C. glutamicum, cells of an overnight pre-culture were washed with 0.9 % (w/v) NaCl (saline) and then inoculated into minimal medium (Eikmanns et al, 1991b) containing glucose or maltose at the concentrations indicated in Results. Cultivation was done aerobically at 30 uC as 250 ml cultures in a 'fedbatch-pro' parallel fermentation system from DASGIP, as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…E. coli and all pre-cultures of C. glutamicum were grown aerobically in TY complex medium (Sambrook & Russel, 2001) at 37 and 30 uC, respectively, as 60 ml cultures in 500 ml baffled Erlenmeyer flasks on a rotary shaker at 120 r.p.m. For the main cultures of C. glutamicum, cells of an overnight pre-culture were washed with 0.9 % (w/v) NaCl, and then inoculated into CgXII minimal medium (Eikmanns et al, 1991) containing glucose at the concentrations indicated in Results. C. glutamicum was grown aerobically at 30 uC as 50 ml cultures in 500 ml baffled Erlenmeyer flasks on a rotary shaker at 120 r.p.m., or as 250 ml cultures in a parallel fermentation system (Fedbatch-pro system; DASGIP) as described previously (Seibold et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids used in this study are pUC18 and pUC19 (56), the C. glutamicum-E. coli shuttle vector pEKO (22), cosmid ppc42 (cosmid pHC79 containing a 26-kb chromosomal DNA fragment from C. glutamicum AS019) (20), and pUC-ppcII (pUC8 containing a 4.5-kb DNA fragment from ppc42) (20). The minimal medium used for C. glutamicum has been described previously (23); LB medium (37) was the complex medium for C. glutamicum and for E. coli. When appropriate, ampicillin (50 ,ug/ml) or kanamycin (15 or 50 ,ug/ml) was added to the medium.…”
mentioning
confidence: 99%